2018
DOI: 10.1158/0008-5472.can-17-0988
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 19 Expression in Hepatocellular Carcinoma Is Regulated by Fibroblast-Derived HGF via a MET-ERK1/2-AP1 and SP1 Axis

Abstract: Keratin (KRT) 19 is a poor prognostic marker for hepatocellular carcinoma (HCC); however, regulatory mechanisms underlying its expression remain unclear. We have previously reported the presence of fibrous tumor stroma in KRT19-positive HCC, suggesting that cross-talk between cancer-associated fibroblasts (CAF) and tumor epithelial cells could regulate KRT19 expression. This was investigated in this study using an model of paracrine interaction between HCC cell lines (HepG2, SNU423) and hepatic stellate cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 45 publications
1
64
0
Order By: Relevance
“…Therefore, the present findings suggest that KRT19‐positive HCC cases might be conditioned by the involvement of the HGF/c‐MET/ERK axis, in addition to the innate KRT19 expression in HCCs. A recent study showed that KRT19 expression in HCC was regulated by the cancer‐associated fibroblast‐derived HGF through the c‐MET/ERK/AP1 and SP1 axis, which is consistent with the present findings . These findings might indicate that the HGF/c‐MET/ERK axis is partly involved in the development of KRT19‐expressing HCC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the present findings suggest that KRT19‐positive HCC cases might be conditioned by the involvement of the HGF/c‐MET/ERK axis, in addition to the innate KRT19 expression in HCCs. A recent study showed that KRT19 expression in HCC was regulated by the cancer‐associated fibroblast‐derived HGF through the c‐MET/ERK/AP1 and SP1 axis, which is consistent with the present findings . These findings might indicate that the HGF/c‐MET/ERK axis is partly involved in the development of KRT19‐expressing HCC.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study showed that KRT19 expression in HCC was regulated by the cancer-associated fibroblast-derived HGF through the c-MET/ERK/AP1 and SP1 axis, which is consistent with the present findings. 57 These findings might indicate that the HGF/c-MET/ERK axis is partly involved in the development of KRT19-expressing HCC.…”
Section: E Rk Is Activated By Phosphorylation Of Its Tyrosinementioning
confidence: 93%
“…These 20 genes were extracted and displayed in Table 3. Defensin Beta, Interferon, and Keratin Associated Proteins are known to be strong cancer driver genes [25,26]. Actin and Ribonuclease has been shown to play a significant role in some cancer types [27].…”
Section: Resultsmentioning
confidence: 99%
“…HGF is highly expressed by activated HSCs and involved in promoting HCC proliferation by binding to its receptor c-Met and activating its downstream ERK1/2 signaling [38][39][40][41][42]. In addition, activation of c-Met/ERK pathway can modulate autophagy processes [43,44].…”
Section: Discussionmentioning
confidence: 99%